Seasonal variation and its impacts in rice-growing regions of the Mekong Delta - Van Hong Nguyen; Hoang Phan Hai Yen (International Journal of Climate Change Strategies and Management, 2021)
Purpose – In recent years, agricultural activities in the Mekong Delta have frequently faced the potential risks of drought, saline intrusion and unusually heavy rainfall because of climate change, leading to a decline in crop yield. Therefore, this study aimed to establish rice planting seasons in An Giang, an upper-located province in the Mekong Delta. Design/methodology/approach – The impacts of seasonal variation on the key rice seasons were simulated using the Food and Agriculture Organization-crop model for the OM6976 rice variety grown in the study area. For the simulation, the model combined crop, soil, weather and crop management data. Findings – The results show that seasonal variation because of changes in weather factors leads to alternation in crop yields across the study area. Specifically, the spring and summer rice planting seasons are advanced by one to two weeks compared with the baseline, and crop yield increased by 5.9% and 4.2%, respectively. Additionally, planting for the autumn–winter rice season on 3 August increased crop yield by up to 8.1%. Originality/value – In general, rice planting seasons that account for weather factor changes effectively reduce production costs and optimise production.